Proceedings of the 2018 ACM International Conference on Interactive Surfaces and Spaces 2018
DOI: 10.1145/3279778.3279801
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Semi-Transparent Keyboards on a Touchscreen Tablet

Abstract: As tablet computers are hosting more productivity applications, efficient text entry is becoming more important. A soft keyboard, which is the primary text entry interface for tablets, however, often competes with applications for the limited screen space. A promising solution to this problem may be a semi-transparent soft keyboard (STK), which can share the screen with an application. A few commercial STK products are already available, but research questions about the STK design have not been explored in dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…The results also indicated that the participants felt no difference at 0 and 25% transparency. The results also agree with Kim and Lee's (2018) assertion that transparency below 50% would have little impact on user experience. In addition, all participants found that both dynamic prompt effects and the degree of background transparency of hover feedback designs were interesting and trustworthy.…”
Section: Discussion Of Subjective Evaluationsupporting
confidence: 89%
See 1 more Smart Citation
“…The results also indicated that the participants felt no difference at 0 and 25% transparency. The results also agree with Kim and Lee's (2018) assertion that transparency below 50% would have little impact on user experience. In addition, all participants found that both dynamic prompt effects and the degree of background transparency of hover feedback designs were interesting and trustworthy.…”
Section: Discussion Of Subjective Evaluationsupporting
confidence: 89%
“…That is, the greater the percentage, the more transparent it is. Kim and Lee (2018) argued that transparency can expand the presentation of information over the limited screen size, and that transparency higher than 50% will affect users' reading, considering the screen size. In a virtual environment interface, operations over a translucent map are much more accessible than opaque maps (Chen and Chen, 2019).…”
Section: Related Workmentioning
confidence: 99%
“…That is, the smaller the percentage, the less transparent it is. Kim and Lee (2018) argued that pop-up windows with transparency effects can reduce the occlusion of the underlying background of the interface. Early research found that windows with reasonable transparency can expand the presentation of information on a limited screen size (Harrison et al, 1995).…”
Section: Transparencymentioning
confidence: 99%